Phosphate Assay Kit in One Cell for Electrochemical Detection of Intracellular Phosphate Ions at Single Cells - Xu, Haiyan; Yang, Dandan; Jiang, Dechen; Chen, Hong-Yuan (Frontiers in Chemistry, 2019)
In this paper, phosphate assay kit in one cell is realized for the electrochemical detection of intracellular phosphate ions at single cells. The components of phosphate assay kit, including maltose phosphorylase, maltose, mutarotase and glucose oxidase, are electrochemically injected into a living cell through a nanometer-sized capillary with the ring electrode at the tip. These components react with phosphate ions inside the cell to generate hydrogen peroxide that is electrochemically oxidized at the ring electrode for the qualification of intracellular phosphate ions. An average 1.7 nA charge was collected from 8 individual cells suggesting an intracellular phosphate concentration of 2.1 mM. The establishment in the electrochemical measurement of phosphate ions provides a special strategy to monitor the fluctuation of intracellular phosphate at single cells, which is significant for the future investigation of phosphate signal transduction pathway.